The Influence of the Level of Injury on the Selection of Recipient Vessels in Severe Open Fractures of the Tibia and Foot - Hayashi, Kota; Futamura, Kentaro; Tsuchida, Yoshihiko; Nishida, Masahiro; Hasegawa, Masayuki; Suzuki, Takafumi; Tsuihiji, Kanako; Ogawa, Takashi; Sato, Ryo (Journal of Reconstructive Microsurgery, 2025)
The selection of recipient vessels is critical for the success of free flap transfer in lower extremity reconstruction following trauma. We hypothesized that variations in soft tissue, vascular, and bone injuries across different injury levels influence recipient vessel selection. This study aimed to investigate the injury patterns and recipient vessel selection at different injury levels.A retrospective analysis was performed on patients with acute open tibial fractures (Gustilo IIIB/C) and mangled foot injuries treated at a single trauma center between 2013 and 2022. Injury levels were classified as proximal tibia (P/3), middle tibia (M/3), distal tibia (D/3), and foot injuries. We analyzed injury patterns by level and defined recipient vessel selection as the primary outcome.A total of 91 limbs from 88 patients were analyzed (P/3: 10, M/3: 39, D/3: 18, foot: 24). M/3 injuries were the most severe, with extensive compartment involvement (p < 0.01) and bone loss in 49% of cases, whereas P/3 injuries were the least severe. The distal posterior tibial artery was predominantly used in P/3 injuries, the proximal posterior tibial artery was most frequently used in M/3 and D/3 injuries, and the anterior tibial artery was used primarily for foot injuries (p < 0.01). Vein grafts were required exclusively in M/3 cases, with intraoperative vascular disturbances occurring in 33%. Postoperative vascular complications ranged from 6 to 20%, with an overall flap survival and limb salvage rate of 95%.Among the findings of this study, key findings were that M/3 injuries were the most severe, and P/3 injuries had favorable outcomes with distal posterior tibial artery anastomosis. Injury patterns and recipient vessel selection show distinct, level-specific differences in severe open fractures of the tibia and foot.
Keywords: open tibial fracture; mangled foot injury; lower extremity reconstruction; free tissue transfer; free flap; recipient vessel